Kinetic approach for the vapor pressure lowering by non volatile solutes - Donati, Edgardo Ruben (2010)
In most basic chemistry courses a kinetic approach is used to explain the vapor pressure lowering for solutions with a non volatile solute. This approach has been considered intrinsically incorrectfor many years based on several objections. We consider that this objections are based on a misinterpretation of the kinetic model. In this paper we will show in detail this model to refute those objections and show that the kinetic approach can be a suitable teaching tool for explaining vapor pressure lowering in ideal solutions of non volatile solutes.